Spectral Analysis of Blood Glucose using Noninvasive Technique - Bavkar, Vandana C; Shinde, AA (International Journal of Computer Sciences and Engineering, 2025)
Diabetes is condition that affects your body’s ability to consume the energy present in our diet. Glucose gives energy to your body cells. Body cells need insulin that is present in our blood for getting glucose and utilizes it for energy. Increase of glucose in blood can damage the small blood veins in your kidneys, heart. Blood glucose level can be monitored by two methods namely invasive and noninvasive methods. Currently invasive glucose monitoring methods are widely used. In this method, the skin is pricked to draw blood and put collected drop into a measurement device. Invasive blood glucose measurement methods are highly accurate and common but they are very uncomfortable. For this reason research on noninvasive method is being carried out worldwide. This method is painless and finger pricking is avoided. A noninvasive method based on NIR technique using occlusion is proposed. The body site is ear lobe or finger. The output of optical signal is analyzed by performing FFT analysis.